Analisis Penerapan Supply Chain Management Studi Kasus Pada Perusahaan Retailer - Endang Hariningsih, Fahmy Radhi (Universitas Muhammadiyah Yogyakarta, 2015)
Objectif of this study is explore the implementation of SCM in retail companies and also its performance assessment by using the method of SCOR Level 1 customer facing aspects. The study was conducted in Matahari Department Store and Supermarket.The research was done by searching the primary and secondary data through interviews with the company participant. Matahari Department Store and Supermarket has SOPs to organize the integration of all the relationship with supply chain participant in supporting the business needs of consumers. Performance Level 1 customer facing aspects of the high performance delivery of components for the Jakarta area in 2011 amounted to 99, 09%, while for outside Jakarta amounted to 99,97%.Keywords: supply chain management, retailer, SCOR